Серебряный век в русской литературе и культуре конца XIX - первой половины XX вв = Silver Age in Russian Literature and Culture in the Late 19th Century and the First Half of the 20th Century К 90-летию со дня рождения З. Г. Минц = On the 90th Birth Anniversary of Zara Minz - Pild, Lea; Stepaništševa, Tatjana (Acta Slavica Estonica, 2018)
Acta Slavica Estonica is an international series of publications on current issues of Russian and other Slavic languages, literatures and cultures. The first section of this volume contains articles on the history, poetics and reception of the Silver Age in Russian literature and culture in the late 19th century and the first half of the 20th century. In the second section, titled "It was impossible not to Love Zara Grigoryevna...", several students of Zara Minz share their memories of her. The third section addresses issues of translation and intermediality in Russian and European culture.